2018
DOI: 10.1016/j.bja.2018.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Liberal fluid fasting: impact on gastric pH and residual volume in healthy children undergoing general anaesthesia for elective surgery

Abstract: NCT02603094.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 25 publications
(28 reference statements)
3
62
0
1
Order By: Relevance
“…2,15 Encouraging fluid intake until premedication decreases fasting times, but this practice must be weighed against the risk of increased gastric residual volumes if fasting times are 30 min or shorter. 16,17 Our findings complement earlier studies that examined the effects of prolonged fasting in anesthetized children. Higher mean arterial pressures were observed after induction of anesthesia in a cohort of "optimized fasting management" children with fasting times that were significantly shorter than a preoptimization group.…”
Section: Discussionsupporting
confidence: 84%
“…2,15 Encouraging fluid intake until premedication decreases fasting times, but this practice must be weighed against the risk of increased gastric residual volumes if fasting times are 30 min or shorter. 16,17 Our findings complement earlier studies that examined the effects of prolonged fasting in anesthetized children. Higher mean arterial pressures were observed after induction of anesthesia in a cohort of "optimized fasting management" children with fasting times that were significantly shorter than a preoptimization group.…”
Section: Discussionsupporting
confidence: 84%
“…This project was undertaken as a Quality Improvement Initiative and as such does not constitute human subjects research. Safety considerations were addressed by implementing policies consistent with published evidence and guidelines, and through the balancing measures described above.…”
Section: Methodsmentioning
confidence: 99%
“…The current American Society of Anesthesiologists (ASA) practice guidelines recommend preoperative clear liquid fasting times (CLFT) of at least 2 hours prior to general anesthesia in healthy individuals . An emerging body of evidence suggests that more liberal CLFT can safely be employed; as a result, the major European pediatric anesthesia societies published a consensus statement recommending that healthy children be allowed to drink clear liquids up to 1 hour before elective anesthesia . This statement has since been endorsed by the Society for Paediatric Anesthesia in New Zealand and Australia, and echoed by the European Society for Anaesthesiology …”
Section: Introductionmentioning
confidence: 99%
“…The cutoff value of 1.5 mL kg −1 to indicate a full stomach is based on normal fasting volumes in healthy patients but has no proven link to the risk of pulmonary aspiration. In a recent study, Schmidt et al reported 5.1% of patients allowed clear fluids until premedication to have gastric fluid volume >4 mL kg −1 , compared to no patients in a 2‐hour fasting group. If GCV is a risk factor for pulmonary aspiration, this means that children allowed liberal intake of clear fluids until premedication run a higher risk for perioperative pulmonary aspiration.…”
Section: Discussionmentioning
confidence: 99%